Edukasi Pemilahan Sampah Anak Usia Dini melalui Media Worksheet Interaktif di Desa Dauh Puri Kauh - Kadek Devi Kalfika Anggria Wardani; Lani Theana; Anak Agung Ngurah Eddy Supriyadinata Gorda (Politeknik Piksi Ganesha Indonesia, 2025)
Problems related to waste sorting have always been a problem in various regions. Until now, there is still waste that is not sorted according to its category. Organic waste should not be mixed with inorganic waste. This hinders the TPS from recycling waste. Dauh Puri Kauh Village faces similar problems. Based on the problems experienced by Dauh Puri Kauh Village, sustainable steps are needed to overcome this. The community service team educates children at Werdhi Kumara Kindergarten to create positive habits in the form of waste sorting. The community service activities carried out by the community service team aim to increase awareness and understanding of sorting waste according to category by using worksheets as a learning medium. In implementing this educational activity, the method used by the community service team is the Participatoryy Action Research (PAR) method. The results of this activity have proven effective in increasing the understanding of early childhood children at Werdhi Kumara Kindergarten. The use of interactive methods helps them understand the concept of waste sorting more easily and forms habits from an early age.